{2-[Bis(2,4-di-tert-butylphenoxy)phosphanyloxy-κP]-3,5-di-tert-butylphenyl-κC1}{3,3′-di-tert-butyl-5,5′-dimethoxy-2,2′-bis[(1,1,2,2-tetraphenylethane-1,2-dioxy)phosphanyloxy-κP]biphenyl}rhodium(I) toluene-d8 2.7-solvate - Detlef Selent; Anke Spannenberg; Armin Börner (IUCrData, 2016)
The molecule of the title compound, [Rh(C42H62O3P)(C74H68O4P2]·2.7C7D8, consists of two phospharhodacyclic substructures sharing the Rh atom, which are formed by coordination/ortho-metallation of a triaryl phosphite, and by the coordination of a rigid bisphosphite, respectively. The metal displays a tetrahedrally distorted square-planar coordination geometry. A tert-butyl group shows rotational disorder over two positions with refined site occupancy of 0.561 (3):0.439 (3). Two partial-occupancy toluene solvent molecules are disordered over two orientations with site occupancies of 0.5:0.3 and 0.5:0.4, respectively. Intramolecular C—H...O hydrogen bonds are observed. In the crystal, complex molecules and toluene solvent molecules pack as alternating layers parallel to the ac plane.